SOCIAL EFFECTS AND BEHAVIORAL TRANSFORMATION OF CUSTOMERS (Marketing Jurnali, 2025)
Customers, especially those in consumer markets have tremendous choice, with their needs and wants satisfied through products and services offered by many brands. The battle for the consumers mind is further amplified owing to social forces — friends, online communities, influencers, and visible signals — which significantly change what customers want and how they act. This paper attempts to explain the key impact of social influence works, uses research-based evidence to validate such hypotheses, and illustrates real-world change through three short case studies. It suggests practical steps for companies and directions for researchers.